Development of a High-Throughput Cytometric Screen to Identify Anti-Wolbachia Compounds: The Power of Public–Private Partnership. (June 2019) - Clare, Rachel H.; Clark, Roger; Bardelle, Catherine; Harper, Paul; Collier, Matthew; Johnston, Kelly L.; Plant, Helen; Plant, Darren; McCall, Eileen; Slatko, Barton E.; Cantin, Lindsey; Wu, Bo; et al.
The Anti- Wolbachia (A·WOL) consortium at the Liverpool School of Tropical Medicine (LSTM) has partnered with the Global High-Throughput Screening (HTS) Centre at AstraZeneca to create the first anthelmintic HTS for neglected tropical diseases (NTDs). The A·WOL consortium aims to identify novel macrofilaricidal drugs targeting the essential bacterial symbiont ( Wolbachia ) of the filarial nematodes causing onchocerciasis and lymphatic filariasis. Working in collaboration, we have validated a robust high-throughput assay capable of identifying compounds that selectively kill Wolbachia over the host insect cell. We describe the development and validation process of this complex, phenotypic high-throughput assay and provide an overview of the primary outputs from screening the AstraZeneca library of 1.3 million compounds.